Precision Farming Enables Climate-Smart Agribusiness - Aisenberg, Igal (International Finance Corporation, Washington, DC, 2018)
Emerging market countries, particularly India and nations in Sub-Saharan Africa, can benefit from advanced farming technologies that mitigate the effects of climate change and protect environmental resources. Water scarcity is an issue that can be overcome by adopting climate smart technologies such as micro-irrigation. There are several precision agriculture investment opportunities available to the private sector, including agricultural extension via digital advisory services, drip irrigation, solar pumps, and crop and soil monitoring. Climate smart farming techniques can increase agricultural productivity and farmer income, make rural communities more resilient, and mitigate climate change. Precision agriculture is part of the solution to feeding a population that is growing faster than available land supply, while also ensuring the sustainable use of water and energy.